Embedding Exposed Subcutaneous Venous Ports in the Pectoral Muscle: A Practical and Stable Technique for Coverage - Osman KELAHMETOĞLU; Ahmet DEMİR; Çağlayan YAĞMUR; Yener DEMİRTAŞ; Ethem GÜNEREN (Bezmiâlem Science, 2017)

(untitled)
Objective:The aim of this study was to present our experience in embedding exposed subcutaneous venous ports in the pectoral muscle.Methods:In this study, six patients who consulted between January 2006 and November 2013 for exposed subcutaneous venous ports were retrospectively evaluated. The ports were placed in the pectoral muscle.Results:The patients were followed up for 4–9 months. Oncologic chemotherapies were initiated at the end of the third week after surgery.Conclusion:With the results of our preliminary observations, we believe that embedding exposed subcutaneous venous ports in the pectoral muscle is a practical and safe method for cachectic patients.